MANAJEMEN PERPUSTAKAAN DALAM PENINGKATAN MINAT KUNJUNG SISWA - Saskia Muslikhul Hasanah; Moh. Syamsul Falah (Lembaga Pengembangan Kinerja Dosen, 2025)
The library plays a crucial role in supporting the educational process in schools, particularly as a source of information and knowledge for students. However, in the era of globalization, students' interest in visiting the library is facing challenges, necessitating appropriate managerial strategies to keep the library relevant and appealing. This study aims to analyze library management in increasing students' interest in visiting the library at SMA A Wahid Hasyim Tebuireng Jombang. This research employs a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data display, and conclusion drawing. The validity of the data is ensured through source triangulation, time triangulation, and technique triangulation. The findings reveal that library management, which includes planning, organizing, implementation, and supervision, significantly contributes to increasing students' interest in visiting the library. Strategies such as updating book collections, creating a comfortable space, implementing literacy programs, and Adequate facilities are highly effective in attracting students' interest. The implications of these findings indicate that effective library management can create an enjoyable learning environment and enhance the literacy culture among students.